Spectrum of Wilson’s Disease in Children Admitted with Liver Disease in a Tertiary Care Hospital of Bangladesh - Jahan, Rifat; Hoque, Salina; Rahman, Bazlur; Ferdousi, Asma; Datta, Mitra; Karim, ASM Bazlul (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Wilson Disease (WD) is a rare genetic disorder found in children and high index of suspicion is needed to screen for such diseases in any child presents with liver diseases after the age of 5 years. This study was aimed to find out the frequency and profile of WD in children admitted with liver diseases at a tertiary care hospital of Bangladesh. Materials and methods: This cross sectional descriptive study was carried out at the Department of Paediatric Gastroenterology and Nutrition, BSMMU in 166 consecutively admitted children with predominant liver diseases aged 3- 14 years. Diagnosis of WD was considered as presence of two of the following 3 criteria: i) Presence of KeyserFleischer ring by slit lamp examination. ii) Low serum ceruloplasmin level (<20mg/dl). iii) Urinary copper excretion of >1200 µgm /24 hours after D-penicillamine challenge. Results: Most frequent liver disease was infective hepatitis (50%) followed by WD detected in 30 (18%) patients. Mean age of the cases of WD was 10.2 (±2.7) years with 66.7% male patients. The most common presenting features of WD cases were jaundice (53.3%). Twenty two (66.7%) patients present with purely hepatic and 10 (33.3%) with both hepatic and neurological manifestation. Low serum ceruloplasmin level was found in 66.7% and 24 hours urinary copper excretion of >1200 µgm/day was found in 86.7% cases. Conclusion: WD was found to be common causes of liver disease next to infective hepatitis. JCMCTA 2020 ; 31 (2) : 54-58